Attitudes towards quechua in the students of Communication Sciences from the Universidad Nacional del Centro del Perú - Vilcapoma Chambergo, José (2017)
The article addresses the attitude university students have towards quechua. The research conducted was of basic type, descriptive level and cross-sectional design (2017); it had as objective to determine the acceptance, indifference (neutrality) or rejection towards quechua, a native and official language of the Peruvian State. It was used as a tool a survey of 26 questions with a Likert scale adapted from Aliaga (2012) that evaluates the cognitive, affective and reactive dimensions through positive and negative questions that give us a score to determine what the student's attitude is. The validity of the instrument was determined by expert judgment through Aiken’s V coefficient, which got a value of 0.75, and its reliability, through the Cronbach’s alpha, which yielded 0.68. The population was constituted by 390 students, from which, by simple stratified sampling, it was obtained a sample of 180 students, 74 male and 106 female. The study concludes that the students from the faculty of Communication Sciences from the Universidad Nacional del Centro del Perú predominantly (53.89 %) have a positive attitude towards quechua; the neutral attitude reached 26.67 %, and the negative one, 19.44 %. In addition, the highest incidence of the positive attitude occurs in women (57.55 %), compared to men (48.65 %); the neutral attitude is similar in women (26.42 %) and men (27.03 %); while the negative attitude presents a higher rate in men (24.32 %) than in women (16.04 %).   DOI: https://doi.org/10.31876/sl.v3i1.7